Palladium/Charcoal-Catalysed Olefin Reduction for the Simple and Efficient Synthesis of Substituted gem-Diborylalkanes - Das, Kanak Kanti; Ghorai, Debraj; Mahato, Somenath; Panda, Santanu (Synthesis, 2023)
gem-Diborylalkanes have recently emerged as valuable synthons for diverse C–C bond-forming reactions. They represent an important class of bifunctional reagents that can be applied for the synthesis of simple to complex skeletons. Herein, we report a Pd-catalysed hydrogenation method for the synthesis of gem-diborylalkanes from the corresponding gem-diborylalkenes, which are themselves prepared from the corresponding aldehydes and ketones using known procedures. In addition, transformations of two representative gem-diborylalkane products are discussed leading to a range of functionalised derivatives.
Keywords: vinyl geminal B(pin); alkyl geminal B(pin); aryl geminal B(pin); heteroaryl geminal B(pin); reduction; palladium/carbon